The Quality Of Baked Brownies Produce From The Subtitution Of Milit Flour - Hazzarah, Fanessha; Elida, Elida; Gusnita, Wiwik; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This study aims to analyze the effect of  25%, 50%, and 75% substitution of jewawut flour on the quality of the, aroma, texture and taste of the baked brownies produced. This type of research is an experiment using a completely randomized design method. The type of data used is primary data obtained from 3 expert panelists by filling out the organoleptic test format. Analysis of the data used is ANOVA, if there is a significant effect, continue with Duncan's test. The results showed there was no effect on the quality of the aroma, texture (congested), texture (dry) and taste of the baked brownies produced. The results of the best steamed brownies in the X3 treatment were in the sweetness category, tasted chocolate, and dark brown in color. It is suggested to the next researcher to process steamed brownies using a substitution of 75% of the amount of wheat flour used.